Sardinian Lives Matter: Dynamics and Reactions in an Italian Internal Colony. Issue 2 (1st September 2021) - Lai, Luca; Watson, Sharon
Abstract: Sardinia had five centuries of independence up until the fifteenth century, and thereafter partial institutional autonomy until 1847. With its inclusion in the Italian state, Sardinia's cultural, economic, institutional and political systems make it uniquely colonial in comparison to other ethnic/national minorities across Europe (Basque, Welsh, Catalan, etc.), leaving limited real choices for development to the locals and constraining what is seen as real and attainable for its future (Escobar 2020 ). This contribution demonstrates how Sardinia is an internal colony of Italy. We provide examples of decolonisation initiatives and provoke further interrogation on the ways in which the Black Lives Matter movement (and other efforts) are sustaining alternative visions for Sardinians' political, economic, cultural and social future.